Letter from Carl D. Duncan to Patricia Whiting, January, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan uses this letter to express his appreciation for Whiting and their father-daughter relationship. He also briefly mentions observations of some kittens and reading a book on Western Civilization that he hoped to study with Whiting.